The state of the human psyche in accordance with Article 5 (1(a)) of the human regulation of the European Union on Artificial Intelligence - Bulgakova, Daria (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2023)
The legal course of the European Union has been established to ban AI systems that use subliminal techniques. The concept of “subliminal methods”, “beyond the limits of human consciousness” and “material distortion” in the context of damage to the psyche is explained through the assessment of the behavior of a person who has suffered or may potentially suffer psychological damage. The need to expand the scope of banning the use of AI systems is emphasized.
Keywords: prohibition of AI systems; consciousness; subliminal techniques; psychological harm assessment; biometric data processing; biometric psychography